PENGARUH FAKTOR FUNDAMENTAL TERHADAP RETURN SAHAM PADA PERUSAHAAN INDEKS KOMPAS100 YANG TERDAFTAR DI BURSA EFEK INDONESIA - B31112021, NILA MONICA (Jurnal Manajemen Update, 2016)
This study aims to investigate the effects of Debt to Equity Ratio (DER), Dividend Payout Ratio (DPR), Net Profit Margin (NPM), Return On Asset (ROA) and Total Assets Turnover (TATO), both partially and simultaneously on Stock Return of index Kompas 100 companies listed in Indonesia Stock Exchange. The research sample, consisting of 33 companies, was selected by means of the purposive sampling technique with the research period of 2011-2014. The data analysis technique was the panel data regression analysis technique using the programs of SPSS 16 and Eviews 9. The result of this study indicate that DER have significant and positive effect on stock return. DPR haven't significant and positive effect on stock return. NPM have significant and positive effect on stock return. ROA haven't significant and negative effect on stock return. TATO haven't significant and positive effect on stock return. DER, DPR, NPM, ROA, and TATO simultaneously have significant effects on stock return. The coefficientÂ  determination indicates the percentage of 14%, which means 86% stock return variable influenced by other variables outside of this research. Keywords : Stock Return, Debt to Equity Ratio (DER), Dividend Payout Ratio (DPR), Net Profit Margin (NPM), Return On Asset (ROA) and Total Assets Turnover (TATO).